Effect of Problem-Based Learning Assisted By E-LKPD Wizer.me On Students Mathematical Literacy Skills - Setyawardani, Ika Febby; Edy, Sarwo (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
The purpose of this study was to determine how the mathematical literacy skills of junior high school students were affected by Problem Based Learning assisted by E-LKPD with Wizer.me. This research was conducted quantitatively, quasi-experimental type, with the design used nonequivalent control group pretest-posttest. This study focuses on eighth-grade students from Manbaul Ulum Gresik Islamic Junior High School, which has 128 students. In this study, the samples used were class VIII A with 31 students as the control class and class VIII C with 28 students as the experimental class, using simple random sampling. The research data collection used test instruments in the form of Pretest and Posttest to determine students' mathematical literacy skills. In technical research, the data analysis used is data analysis, normality test, and Mann-Whitney non-parametric test. The results showed that there were significant differences in the control class and the experimental class. So it can be concluded that learning mathematics using Problem Based Learning assisted by E-LKPD using Wizer.me has an effect on students' mathematical literacy skills.